Projected heatwaves in Xinjiang Uygur autonomous region, China - Dong, Diwen; Tao, Hui; Zhang, Zengxin; Mondal, Sanjit Kumar (Frontiers in Earth Science, 2024)
Heatwaves (HWs) are the serious natural disaster that exert great impacts on the human health and social economy. Projecting future changes in HWs is crucial for the development of effective adaptation strategies. This study investigates the variations in HWs for three time periods (nearterm, mid-term, and long-term) in Xinjiang under four Shared Socioeconomic Pathways (SSP1-2.6, SSP2-4.5, SSP3-7.0 and SSP5-8.5) using the heatwave index (HI) and 17 climate models. To enhance confidence in HWs projection, we evaluate the performance of 17 climate models in simulating HWs in terms of interannual variability and spatial patterns using interannual variability skill score (IVS) and distance between indices of simulation and observation (DISO), respectively. Compared to the observed data, the overall performance of the multi-model ensemble (MME) is outperformed by individual models, although most models effectively capture the characteristics of HWs. Projections indicate that HWs in Xinjiang will become more prolonged and severe.Specifically, in the long-term under SSP5-8.5 scenario, HWF and HWD are projected to reach 7.5 times and 61 days, respectively. The spatial distribution of HWs exhibits significant heterogeneity, with high-value regions primarily distributed in eastern Xinjiang and the eastern part of southern Xinjiang. Although the HWs area is projected to expand under all scenarios, the spatial distribution pattern is anticipated to remain largely unchanged. These findings provide a comprehensive assessment of future variations in HWs, which are necessary for improving regional adaptive capacity to extreme heat risk.